Sozialpolitik bei Budgetengpässen und Fiskalpakt - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2012)
– Europe is in the throes of budgetary consolidation, tightening its fiscal rules. It could not prevent the recession of 2012 and the inexorable growth of debt, especially in Southern Europe, while unemployment spreads and the social gap widens. Social policy is mostly a national matter, but is nevertheless increasingly shaped by European rules and facing some big-scale challenges. New responsibilities can no longer be funded by additional taxes as state expenditure already makes up 50 percent of the economic performance and is not even fully covered by revenues. New responsibilities can be undertaken only when problems are identified early on or even prevented outright, e.g., by an education policy or preventive health scheme, before the costs of unemployment, illness and nursing actually arise. Investment in the future and youth employment decide on the economy's competitiveness as much as on the acceptance of the European model, especially with the young. The current European growth path is socially imbalanced and chained to an ever greater consumption of resources. Modern social policy is not an isolated subpolicy but goes together with education and innovation policy and is increasingly turning international. In order to actively respond to new social problems even in a phase of budgetary consolidation as well as limit their costs it would be useful to have a social pact supplementary to the fiscal pact at a European level.
Keywords: 330; Social policy; budget consolidation; fiscal compact; social compact; Sozialpolitik; Haushaltskonsolidierung; Soziale Folgen; Soziale Ungleichheit; EU-Staaten